Figurative Language Implemented In Eminem’s Songs Lyrics - Aisyarah, Dinda Nur; Wahyuni, Sri (English Journal Antartika, 2024)
This paper aims to identify and analyze the figurative language implemented in Eminem’s songs “Mockingbird,” “When I’m Gone”, and “Hailie’s Song”. Using a descriptive qualitative research method, this study collected data through careful listening and reading of the song's lyrics. This process involved identification, categorization, and analysis of the lyrics, leading to conclusions about the theme song's explanation and interpretation. The theoretical framework is based on Hurford and Heasley’s (1983) semantic theory, with the meaning approach presented by Geoffrey N. Leech. The findings reveal how figurative language intricately depicts themes of fame, family issues, and father’s sacrifice, offering deeper insights into the artist’s emotional landscape.